Defining the relative utility of lumbar spine surgery: A systematic literature review of common surgical procedures and their impact on health states. (November 2021) - Gates, Marcus; Tang, Alan R.; Godil, Saniya S.; Devin, Clint J.; McGirt, Matthew J.; Zuckerman, Scott L.
Highlights: Lumbar spondylosis leads to decreased quality of life. Among common medical diagnoses, lumbar spondylosis had the lowest EQ-5D score (0.36). The greatest QALY gains were seen in lumbar spine surgery and hip/knee arthroplasty. Abstract: Degenerative lumbar spondylosis is a common indication for patients undergoing spine surgery. As healthcare costs rise, measuring quality of life (QOL) gains after surgical procedures is critical in assessing value. We set out to: 1) compare baseline and postoperative EuroQol-5D (EQ-5D) scores for lumbar spine surgery and common surgical procedures to obtain post-operative quality-adjusted life year (QALY) gain, and 2) establish the relative utility of lumbar spine surgery as compared to other commonly performed surgical procedures. A systematic literature review was conducted to identify all studies reporting preoperative/baseline and postoperative EQ-5D scores for common surgical procedures. For each study, the number of patients included and baseline/preoperative and follow-up mean EQ-5D scores were recorded, and mean QALY gained for each intervention was calculated. A total of 67 studies comprising 95, 014 patients were identified. Patients with lumbar spondylosis had the worst reported QOL at baseline compared to other surgical cohorts. The greatest QALY gain was seen in patients undergoing hip arthroplasty (0.38), knee arthroplasty (0.35) and lumbar spine surgery (0.32), nearly 2.5-fold greater QALY gained than for all other procedures. The low preoperative QOL, coupled with the improvements offered with surgery, highlight the utility and value of lumbar spine surgery compared to other common surgical procedures.